Functional connectivity development along the sensorimotor-association axis enhances the cortical hierarchy - Luo, Audrey C.; Sydnor, Valerie J.; Pines, Adam; Larsen, Bart; Alexander-Bloch, Aaron F.; Cieslak, Matthew; Covitz, Sydney; Chen, Andrew A.; Esper, Nathalia Bianchini; Feczko, Eric; Franco, Alexandre R.; Gur, Raquel E.; et al. (Nature communications, 2024)
Human cortical maturation has been posited to be organized along the sensorimotor-association axis, a hierarchical axis of brain organization that spans from unimodal sensorimotor cortices to transmodal association cortices. Here, we investigate the hypothesis that the development of functional connectivity during childhood through adolescence conforms to the cortical hierarchy defined by the sensorimotor-association axis. We tested this pre-registered hypothesis in four large-scale, independent datasets (total n = 3355; ages 5–23 years): the Philadelphia Neurodevelopmental Cohort ( n = 1207), Nathan Kline Institute-Rockland Sample ( n = 397), Human Connectome Project: Development ( n = 625), and Healthy Brain Network ( n = 1126). Across datasets, the development of functional connectivity systematically varied along the sensorimotor-association axis. Connectivity in sensorimotor regions increased, whereas connectivity in association cortices declined, refining and reinforcing the cortical hierarchy. These consistent and generalizable results establish that the sensorimotor-association axis of cortical organization encodes the dominant pattern of functional connectivity development. Human cortical maturation is organized along the sensorimotor-association axis. Here, the authors investigate in multiple cohorts if the development of functional connectivity during adolescence conforms to this hierarchy.